Political business cycles at the municipal level - Veiga, Linda Gonçalves (2004)
This article tests for the existence of rational political business cycles models using a large and unexplored data set of Portuguese municipalities. The data set is well-suited for this purpose because it provides a high level of detail on expenditure items, because Portuguese municipalities are homogeneous with respect to policy instruments and institutions and follow an exogenously determined election schedule. Estimation results clearly reveal the existence of opportunistic behaviour by local governments. Expenditures increase in pre-election periods, especially on items that are highly visible to the electorate (e.g., highways and streets). This suggests an effort to signal competence and improve chances of re-election.